International Survey of Operative Practices for Otologists and Neurotologists During the COVID-19 Crisis. Issue 8 (September 2021) - Ridge, Sarah E.; Chari, Divya A.; Kozin, Elliott D.; Remenschneider, Aaron K.; Adunka, Oliver F.; Aristegui, Miguel; Chang, Wai Tsz; Cheng, Yen-Fu; Chung, Jong Woo; Cohen, Michael S.; Crowson, Matthew G.; Golub, Justin S.; et al.
Abstract : Objective: To investigate the influence of the COVID-19 pandemic on operative practices of otology and neurotology providers internationally. Study Design: Cross-sectional survey. Methods: A 78-question survey was distributed to otologists and neurotologists between May 12, 2020 and June 8, 2020 to assess the impact of the pandemic on surgical practices. Sections within the survey delineated time periods: prior to the crisis, onset of the crisis, during the crisis, postcrisis transition. Results: Of 396 survey respondents, 284 participants from 38 countries met inclusion criteria. Respondents were 16.9% female and 82.4% male, with a most common age range of 40 to 49 years (36.3%). 69.8% of participants had been in practice for over 10 years and most respondents worked in an academic medical center (79.2%). The average operative weekly caseload was 5.3 (SD 3.9) per surgeon prior to the crisis, 0.7 (SD 1.2) during the COVID-19 crisis, and 3.5 (SD 3.3) for those who had begun a postcrisis transition at the time of survey administration ( p < 0.001). 71.5% of providers did not perform an elective otologic or neurotologic operative procedure during the initial crisis period. 49.8% reported modifying their surgical technique due to the COVID-19 pandemic. Use of powered air-purifying respirators and filtering facepiece 2 or 3 (FFP2/FFP3) respirators were in minimal supply for 66.9% and 62.3% of respondents, respectively. Conclusion: The COVID-19 pandemic impacted the otology and neurotology community globally, resulting in significant changes in operative volume and case selection. Modification of surgical technique and shortages of personal protective equipment were frequently reported. Abstract : Supplemental Digital Content is available in the text